Improvement in low back movement control, decreased pain and disability, resulting from specific exercise intervention - Luomajoki Hannu; Kool Jan; de Bruin Eling D; Airaksinen Olavi (BMC, 2010)
Abstract Background The study was conducted to assess whether patient-specific functional impairment and experienced daily disability improved after treatment to address active movement control of the low back. Method A prospective study was carried out in two outpatient physiotherapy practices in the German-speaking part of Switzerland. 38 patients (17 males and 21 females) suffering from non-specific low back pain (NSLBP) and movement control impairment were treated. The study participants had an average age of 45 ± 13 years, an average height of 170 ± 8 cm and an average weight of 73 ± 15 kg. Patients were assessed prior and post treatment. Treatment was aimed at improving movement control of the lumbar spine, pain and disability. Six physiotherapists treated each patient on average nine times (SD 4.6). Treatment effects were evaluated using a set of six movement control tests (MCT), patient-specific functional pain scores (PSFS) and a Roland and Morris disability questionnaire (RMQ). Means, standard deviations, confidence intervals and paired t-tests were calculated. The effect size (d) was based on the change between t1 (time prior intervention) and t2 (time post intervention) using a significance level of p < 0.05, with d > 0.8 being considered a large effect. Power calculations were performed for type I & II error estimation. Results Movement control (MCT) showed a 59% improvement from 3.2 (max 6) to 1.3 positive tests (d = 1.3, p < 0.001), complaints (PSFS) decreased 41% from 5.9 points (max 10) to 3.5 (d = 1.3, p < 0.001), and disability (RMQ) decreased 43% from 8.9 to 5.1 points (d = 1.0, p < 0.001). Conclusions The results of this controlled case series study, based on prior and post intervention, showed that movement control, patient specific functional complaints and disability improved significantly following specific individual exercise programs, performed with physiotherapeutic intervention. The results obtained warrant performance of a randomized controlled trial (RCT) to substantiate our findings.